2020
DOI: 10.1029/2020ja027990
|View full text |Cite
|
Sign up to set email alerts
|

EMIC Waves in the Earth's Inner Magnetosphere as a Function of Solar Wind Structures During Solar Maximum

Abstract: Here we analyze the statistics of electromagnetic ion cyclotron (EMIC) waves observed in the Earth's inner magnetosphere during coronal mass ejection (CME), high-speed stream (HSS), and quiet solar wind (QSW) conditions in the upstream solar wind (SW). For our analysis we use the EMIC wave observations by the two Van Allen Probes during their first magnetic local time (MLT) revolution. The major results of our analysis are as follows: (1) Criteria to identify the HSS, CME, and QSW conditions in the SW are form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…They formulated criteria to identify the CME, HSS, and QSW conditions in the upstream SW and then categorized each EMIC wave event according to the upstream SW conditions preceding to the event. As expected, they reported that the majority of EMIC wave events were observed during CME conditions in the upstream SW, where the state of the upstream SW is identified as CME if an interplanetary shock, and/or ejecta, and/or a magnetic cloud are observed within the time interval of 18 h preceding the end of an analyzed EMIC wave event (see Gamayunov et al, 2020, for more details). For our analysis of the low frequency ULF waves here we will use those EMFISIS data that include the CME-driven EMIC wave events identified by Gamayunov et al (2020).…”
Section: Magnetic Field Data and Their Analysissupporting
confidence: 58%
See 4 more Smart Citations
“…They formulated criteria to identify the CME, HSS, and QSW conditions in the upstream SW and then categorized each EMIC wave event according to the upstream SW conditions preceding to the event. As expected, they reported that the majority of EMIC wave events were observed during CME conditions in the upstream SW, where the state of the upstream SW is identified as CME if an interplanetary shock, and/or ejecta, and/or a magnetic cloud are observed within the time interval of 18 h preceding the end of an analyzed EMIC wave event (see Gamayunov et al, 2020, for more details). For our analysis of the low frequency ULF waves here we will use those EMFISIS data that include the CME-driven EMIC wave events identified by Gamayunov et al (2020).…”
Section: Magnetic Field Data and Their Analysissupporting
confidence: 58%
“…As expected, they reported that the majority of EMIC wave events were observed during CME conditions in the upstream SW, where the state of the upstream SW is identified as CME if an interplanetary shock, and/or ejecta, and/or a magnetic cloud are observed within the time interval of 18 h preceding the end of an analyzed EMIC wave event (see Gamayunov et al, 2020, for more details). For our analysis of the low frequency ULF waves here we will use those EMFISIS data that include the CME-driven EMIC wave events identified by Gamayunov et al (2020). (Note that EMIC waves do not affect the low frequency ULF waves, and so the statistics of low frequency ULF waves cannot depend on whether or not EMIC fluctuations exist in the data segments analyzed.)…”
Section: Magnetic Field Data and Their Analysissupporting
confidence: 58%
See 3 more Smart Citations